Upregulation of ADAM12 Is Associated With a Poor Survival and Immune Cell Infiltration in Colon Adenocarcinoma - Huang, Zigao; Lai, Hao; Liao, Jiankun; Cai, Jinghua; Li, Baojia; Meng, Linghou; Wang, Wentao; Mo, Xianwei; Qin, Haiquan (Frontiers in Oncology, 2021)
Background: A disintegrin and metalloprotease 12 (ADAM12) is a member of a multidomain protein family, but the mechanisms by which it affects prognosis and immune cell infiltration in patients with colon adenocarcinoma (COAD) remain unclear. Here, our study aimed to analyze the prognostic value of ADAM12 and investigate the correlation between ADAM12 expression and immune cell infiltration in patients with COAD. Methods: Differential expression analyses were performed using the Oncomine and UALCAN databases, and prognostic analyses were conducted using PrognoScan, Gene Expression Profiling Interactive Analysis (GEPIA), and Kaplan–Meier Plotter. Then, the cBioPortal database was used to analyze alterations in the ADAM12 gene, and the STRING and Metascape websites were used to conduct Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses. Additionally, relationships between ADAM12 and the immune microenvironment were evaluated based on the TIMER, GEPIA and TISIDB databases. Results: ADAM12 was overexpressed in COAD tissues, and higher ADAM12 expression correlated with a worse prognosis for patients with COAD. The gene regulatory network suggested that ADAM12 was mainly enriched in extracellular matrix (ECM) organization, ECM proteoglycans, skeletal system development, and ossification, among other pathways. Moreover, ADAM12 expression significantly correlated with the abundance of CD4+ T cells, B cells, CD8+ T cells, neutrophils, macrophages, dendritic cells and their markers, as well as lymphocytes, immunomodulators and chemokines. Conclusions: In colorectal tumors, ADAM12 may play vital roles in regulating the ECM and the recruitment of immune cells, and we suggest that ADAM12 will become a reliable biomarker for determining response to immunotherapy and the prognosis of patients with COAD.